THE EFFECT OF BODY REPOSITIONING ON HEMODYNAMIC STATUS IN PATIENTS WITH VASOPRESSOR THERAPY IN INTENSIVE CARE UNIT - Vica Sari Oktorina; Aan Nuraeni (Belitung Raya Foundation, Indonesia, 2018)
Background: Repositioning the patients every 2 hours were often not implemented during patient care. One of the causes perceived by nurses as contraindications to repositioning in critical patients is the use of vasoactive agents. This condition increases the risk of decubitus, decreased orthostatic stability and muscle atrophy. Objective: The purpose of this study was to identify the effect of body reposition on hemodynamic patients receiving vasopressor therapy in Intensive Care Unit (ICU). Methods: The research method used Quasi Experiment with non-equivalent control group design. The subjects were ICU patients who received vasopressor therapy. The respondents recruited using consecutive sampling technique for a-four-month period and obtained 34 respondents, which was divided into control and intervention group. Data analysis used paired t-test to analyze the difference in the same group and unpaired t-test to test the difference between two groups. Results: Pre-post hemodynamic differences in the intervention group when patients were repositioned from supine to the right lateral and right lateral to left lateral showed p> 0.05. The hemodynamic difference between the control and the intervention group also had p> 0.05. The results showed there were no significant difference. Conclusions: In general, there is no effect of body repositioning on hemodynamic status. Critical nurses can perform body repositioning activities every two hours including in patients with vasopressor therapy to prevent complications of immobilization, still considering contraindication condition.